Синтез та електрокаталітичні властивості наноструктурованих плівок на основі TiO2-Nd - Vorobets, V. S.; Kolbasovа, I. G.; Liniucheva, O. V.; Karpenko, S. V.; Alontseva, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
Nanostructured TiO2 films modified with Nd3+-ions have been produced by sol-gel method and characterized by XRD method. Electrocatalytic activity of electrodes based on prepared films in the oxygen electroreduction have been tested. Improvement of electrocatalytic activity in comparison with unmodified TiO2 has been observed for films with dopant concentrations up to 3%. Synthesized films can be used in electrochemical sensors for the determination of O2 in liquid media.